Effect of storage temperature on seed-borne fungi infestation and seeds vigor on barley (Hordeum vulgare L.) cultivars - لیلا یاری; شهلا هاشمی; عباس زارعیان (علوم و فناوری بذر ایران, 2018)
One of the major factors for the low productivity of seeds is poor seed germination and early seedling mortality due to seed-borne fungi. Several grain-borne fungi, including species of Alternaria, Aspergillus, Fusarium and Penicillium, have been implicated as seedling pathogens of cereals. Experiments were conducted at the seed and Plant certification and Registration Research Institute. Experimental units were arranged factorial in a completely randomized design with two factors (cultivar and storage temperature). The result indicated that interaction between storage temperature × cultivar had significantly affected on seed-borne fungi after three months storage. The seed-borne fungi infestation sach as Asporgilau flavus and Penicillium decreased in all seeds that stored at 20-30C° (alternative temperature), also the Fusarium species infestation was reduced in Usef, Nosrat, and Productive Cultivars seed under storage at 20-30C°, whereas Alternaria alternate infestation was increased in all seeds that stored at 20-30 C° . Meanwhile, normal seedling percentage and seedling vigor were significantly improved by storage seeds at 20-30 C° that it was more pronounced in Sahra and Productive cultivars. Final germination percentage and normal seedling percentage increased, when seed-borne fungi infestation such as Aspergillus flavus,Penicillium sppand Fusarium spp decreased in seed samples. Generally, according to cultivars that examined in this experiment, seed stored at 20-30 C°(alternative temperature) could have maintained their vigour high, it is new founding that could help to control seed-borne fungi (Asporgilau flavus, Penicilliumsppand Fusarium spp) in storage condition also prevent of seed deterioration.